Leveraging the work force using information technology: a financial service case study. (1st September 2004) - Ferguson, Tyler; Lin, Binshan; Chen, Jason C.H.
How can a company maximise its employees' workload, become more efficient, and maximise profits without having to drastically increase the number of employees? This is a problem that many companies face everyday. Companies trying to compete in markets with intense rivalry and small profit margins must fully utilise every employee by maximising efficiency, effectiveness, and work output. Information Technology (IT) is not only changing the way companies operate internally, but also altering the relationships between companies and their suppliers, customers, and other business partners. Thanks to various advances in IT the problem of leveraging the work force has been mitigated. Implementing a successful solution requires more than simply purchasing new computers or software. To effectively use IT a company must undergo a Business Process Reengineering (BPR) that requires vision and dedication. Using the right IT and information systems strategies will help a company leverage its workforce. Fewer employees will be able to manage a greater workload while increasing company profits. This paper focuses on IT and models and examines how they can be used to leverage the work force within Northwest Farm Credit Services, a company that provides quality financial service, thereby enhancing its competitive strategic advantage within the marketplace.